Analisis Pengaruh Korelasi Fiskal Atas Laporan Keuangan Komersial Terhadap PPh Badan Terutang pada PT. Hardjono Patra Jaya - Pringgo Saputro; Iis Dewi Herawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Abstract. The purpose of this study was to determine differences in corporate tax payments payable before and after the fiscal reconciliation of commercial financial statements. By carrying out a fiscal reconciliation, the company can then make financial reports in accordance with applicable tax regulations. In the research conducted, the authors analyzed the data using quantitative and descriptive methods. To obtain the data needed in this writing, the authors carried out data collection activities by means of interviews, documentation and literature studies. The results of this study conclude that there is a difference between profit according to commercial and fiscal. This difference occurs because corrections are made to costs and income.